Analisa Perancangan Sistem Informasi Inventory dengan Metode FIFO (First In First Out) pada Usaha Dagang Retail - Purwati; Sumaryanto; Setiyo Prihatmoko (LPPM Politeknik Pratama Kendal, 2022)
Inventory Information System in a retail trading business plays a fairly important role, especially if the goods sold consist of various types and with a fairly high turnover rate. One of the problems that often arise in an inventory system is that the number and condition of goods available in the warehouse cannot be known with certainty. This can result in goods being stored in the warehouse for too long, excessive, lacking or even running out of inventory. Besides, the use of a good inventory system is expected to reduce the risk of loss or misuse of inventory, because each type of goods has been classified regularly and allows it to be checked at any time. In short, management will be able to quickly and easily find out the existence and changes in the inventory of goods in the event of a purchase and sale of goods.